2003
DOI: 10.1007/s00425-003-1079-3
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the endogenous arginine decarboxylase transcript levels in rice leads to depletion of the putrescine and spermidine pools with no concomitant changes in the expression of downstream genes in the polyamine biosynthetic pathway

Abstract: We investigated whether down-regulation of arginine decarboxylase (ADC) activity and concomitant changes in polyamine levels result in changes in the expression of downstream genes in the polyamine pathway. We generated transgenic rice (Oryza sativa L.) plants in which the rice adc gene was down-regulated by expression of its antisense oat (Avena sativa L.) ortholog. Plants expressed the oat mRNA adc transcript at different levels. The endogenous transcript was down-regulated in five out of eight plant lineage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 30 publications
2
17
1
Order By: Relevance
“…Labeling of the probe, hybridization, washes, and chemiluminescent detection were carried out as described in ref. 10. Membranes were then incubated with CSPD Chemiluminescent Substrate (Roche) and exposed to x-ray film (Fuji) for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Labeling of the probe, hybridization, washes, and chemiluminescent detection were carried out as described in ref. 10. Membranes were then incubated with CSPD Chemiluminescent Substrate (Roche) and exposed to x-ray film (Fuji) for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Hybridization with the Datura adc probe was carried out as described above. Probes for the rice adc and samdc genes were generated by PCR as described (10), and reprobing was performed as described in ref. 22.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In subsequent experiments we used an antisense transgene to reduce OsADC mRNA levels and hence ADC activity, but OsODC, OsSAMDC and OsSPDS mRNA levels remained unchanged. We concluded that altering polyamine levels had no effect on the steady-state mRNA levels of endogenous pathway genes, demonstrating that the endogenous and transgenic pathways were uncoupled Trung-Nghia et al 2003). These data were used to derive a uniform model in which the putrescine pool must exceed a certain threshold to induce the synthesis of spermidine and spermine under stress.…”
Section: Introductionmentioning
confidence: 98%
“…All the genes in the metabolic pathway were shown to function coordinately to produce b-carotene in the endosperm, revealed by the yellow color of the polished rice seed. Capell and colleagues have also used particle bombardment to engineer a complex metabolic pathway, and have created a diverse range of rice germplasm with various genes in the polyamine biosynthetic pathway either over-expressed or suppressed through antisense mechanisms (Capell et al 1998Bassie et al 2000a, b;Noury et al 2000;Lepri et al 2001;Thu-Hang et al 2002;Trung-Nghia et al 2003). Most recently, they have used the data from these numerous lines to synthesize a uniform model of polyamine regulation in plants, based on the simultaneous measurement of endogenous and heterologous gene expression, enzyme activities and polyamine levels (Capell et al 2004).…”
Section: Particle Bombardment Facilitates Simultaneous Multiple Gene mentioning
confidence: 99%